Restructuring of an Agricultural Enterprise: A Case Study of An Agricultural Farm - Ryszard Budzik; Marsel Marks (Communications of International Proceedings, 2022)
The article presents a problem in large farms which are agricultural enterprises. On the example of a specific agricultural enterprise - "Agroland", the analysis of the possibilities of its restructuring was carried out. In order to establish the restructuring plan for the "Agroland" agricultural enterprise, first of all, the financial analysis of the results in recent years was carried out. Then, the type of restructuring was chosen, the restructuring plan was presented, including an estimate of how long the planned investment should take to pay off. The restructuring plan will include financial results, profits, rate of return after the implementation of this plan.
Keywords: Restructuring of An Agricultural Enterprise; Financial Analysis